Socioeconomic Risk Factors for Preterm Birth in Manipur, Northeast India: A Community-Based Study - Devi, Thangjam Chitralekha; Singh, Huidrom Suraj (Journal of Health and Allied Sciences NU, 2023)
Background Preterm birth (PTB) is one of the world's leading health concerns, affecting both the mother and the children. This study was undertaken to determine the prevalence and socioeconomic factors associated with PTB among the Meitei women of Manipur.Materials and Methods A community-based cross-sectional study was conducted in postpartum Meitei women of Manipur. Participants were 126 postpartum women that gave birth to a singleton live-born infant and were classified as women giving birth before 37 weeks of gestation (PTB) and women giving birth at ≥37 weeks (term). Data were compared using univariate analysis, and the association of socioeconomic factors with PTB was determined through multivariate logistic regression using Statistical Package for Social Sciences 25 version software program, and statistical significance was taken at a p-value < 0.05.Results The overall prevalence of PTB is 23.01%, of which 13.79% are of extremely preterm. This study revealed a significant association of PTB with mother's occupation (adjusted odds ratio [AOR] = 4.46, 95% confidence interval [CI]: 1.40–14.26, p = 0.012), tobacco consumption during pregnancy (AOR = 2.90, 95% CI: 1.01–8.33, p = 0.048), having family history of PTB (AOR = 3.14, 95% CI: 1.09–9.04, p = 0.034), and early age at menarche (AOR = 4.26, 95% CI: 1.49–12.12, p = 0.007).Conclusion The study highlights the high prevalence of PTB and its association with various socioeconomic factors. Such community-specific studies should be performed to understand the differential risk factors of PTB to control premature death in under 5 years children and to promote women's reproductive health.
Keywords: Meitei; preterm birth; menarche; tobacco consumption; socioeconomic